Method of Generalized Moment Representations in the Theory of Rational Approximation (A Survey) - Holub, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We give a survey of the method of generalized moment representations introduced by Dzyadyk in 1981 and its applications to Padé approximations. In particular, some properties of biorthogonal polynomials are investigated and numerous important examples are given. We also consider applications of this method to joint Padé approximations, Padé–Chebyshev approximations, Hermite–Padé approximations, and two-point Padé approximations.